OPTIMIZING TEACHER COMPETENCE THROUGH A MADRASAH-BASED MANAGEMENT APPROACH - Ulum, Bahrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In order to realize the achievement of ideal and professional Islamic Religious Education teachers, a managerial approach is needed in order to increase the competence of these teachers, which includes aspects of planning, organizing, supervising. The Madrasah-based management approach is very appropriate to use as an analytical knife in order to increase the competence of Islamic Religious Education teachers. This study uses qualitative research with a descriptive approach. This study aims to analyze and understand about increasing the competence of optimizing teacher competence through a madrasah-based management approach.